Predictors and trends of Caesarean section and breastfeeding in the Eastern Mediterranean region: Data from the cross-sectional Cyprus Women's Health Research (COHERE) Initiative - Swift, Bethan; Taneri, Bahar M.; Cagnan, Ilgin T.; Becker, Christian A.; Zondervan, Krina; Quigley, Maria; Rahmioglu, Nilufer (Public Library Science, 2023)
IntroductionCaesarean section (C-section) is a life-saving procedure when medically indicated but unmet need and overuse can add to avoidable morbidity and mortality. It is not clear whether C-section has a negative impact on breastfeeding and there is limited data available on rates of C-section or breastfeeding from Northern Cyprus, an emerging region in Europe. This study aimed to investigate prevalence, trends and associations of C-section and breastfeeding in this population. MethodsUsing self-reported data from the representative Cyprus Women's Health Research (COHERE) Initiative, we used 2,836 first pregnancies to describe trends in C-section and breastfeeding between 1981 and 2017. Using modified Poisson regression, we examined the relationship between year of pregnancy and C-section and breastfeeding, as well as the association between C-section and breastfeeding prevalence and duration. ResultsC-section prevalence in first pregnancies increased from 11.1% in 1981 to 72.5% in 2017 with a relative risk of 2.60 (95%CI; 2.14-2.15) of babies being delivered by C-section after 2005 compared to before 1995, after full adjustment for demographic and maternal medical and pregnancy related factors. Prevalence of ever breastfeeding remained steady throughout the years at 88.7% and there was no significant association between breastfeeding initiation and the year of pregnancy, or demographic and maternal medical and pregnancy related variables. After full adjustment, women who gave birth after 2005 were 1.24 (95%CI; 1.06-1.45) times more likely to breastfeed for >12 weeks compared to women who gave birth before 1995. There was no association between C-section and breastfeeding prevalence or length. ConclusionPrevalence of C-section in this population is much higher than WHO recommendations. Public awareness campaigns surrounding choice during pregnancy and change in legal framework to allow for midwife-led continuity models of birthing care should be implemented. Further research is required to understand the reasons and drivers behind this high rate.
Keywords: Vaginal Birth; Term; Prevalence; Rates